Bond Strength of Resin Cements to Zirconia Ceramic Using Adhesive Primers. Issue 5 (15th September 2015) - Stefani, Ariovaldo; Brito, Rui Barbosa; Kina, Sidney; Andrade, Oswaldo Scopin; Ambrosano, Gláucia Maria Bovi; Carvalho, Andreia Assis; Giannini, Marcelo
Abstract: Purpose: To evaluate the influence of adhesive primers on the microshear bond strength of resin cements to zirconia ceramic. Materials and Methods: Fifty zirconia plates (12 mm × 5 mm × 1.5 mm thick) of a commercially available zirconium oxide ceramic (ZirCad) were sintered, sandblasted with aluminum oxide particles, and cleaned ultrasonically before bonding. The plates were randomly divided into five groups of 10. Three resin cements were selected (RelyX ARC, Multilink Automix, Clearfil SA Cement self‐adhesive resin cement), along with two primers (Metal‐Zirconia Primer, Alloy Primer) and one control group. The primers and resin cements were used according to manufacturers' recommendations. The control group comprised the conventional resin cement (RelyX ARC) without adhesive primer. Test cylinders (0.75 mm diameter × 1 mm high) were formed on zirconia surfaces by filling cylindrical Tygon tube molds with resin cement. The specimens were stored in distilled water for 24 hours at 37°C, then tested for shear strength on a Shimadzu EZ Test testing machine at 0.5 mm/min. Bond strength data were analyzed statistically by two‐way ANOVA and Dunnett's test (5%). Results: The bond strength means in MPa (± s.d.) were: RelyX ARC: 28.1 (6.6); Multilink Automix: 37.6 (4.5); Multilink Automix + Metal‐Zirconia Primer: 55.7 (4.0); Clearfil SA Cement: 46.2 (3.3); and Clearfil SA Cement + Alloy Primer: 47.0 (4.1). Conclusion: Metal‐Zirconia Primer increased the bond strength of Multilink Automix resin cement to zirconia, but no effect was observed for Alloy Primer using Clearfil SA Cement. RelyX ARC showed the lowest bond strength to zirconia.